Concept model for the second life cycle of vehicles in Palestine - Sughayyer, Momen; Karaeen, Mohammed; Abu Hanieh, Ahmed; AbdElall, Sadiq; Hasan, Hasan (Procedia Manufacturing, 2017)
Old road vehicles in Palestine like most of other countries are inefficient in terms of fuel consumption, unequipped with proper modern passenger safety means and produce high levels of exhaust toxic emissions. One important aspect that needs attention is when these vehicles fail to meet licensing regulations and become a real problem, especially in Occupied Palestine that has a special circumstances and limited resources, hence there is no specific national policy to recycle them. This case is also applicable on badly damaged vehicles by accidents. This paper will present a concept for the second life cycle of vehicle by reusing, remanufacturing, recycling its parts. The model will investigate the vehicle parts by creating data-base system of possible recycling parts. Good condition parts will be available for the second hand use; other parts will be sold as scrap metals. The economic, environmental and social impact of the proposed model will be discussed at the end of the paper.
Keywords: Vehicle recycling; vehicle reused; vehicle remanufacturing; Vehicle second life cycle